2013
DOI: 10.1021/ef301429v
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Darcy-Scale Model of Oil Displacement with Macroemulsion

Abstract: Experiments have shown that injection of oil-in-water macroemulsions can be used as an effective enhanced-oil recovery (EOR) method, with potential increase in the volume of oil recovered. As emulsion drops move through the pore space, they give rise to multiscale flow effects that are commonly associated with mobilization of residual oil and macroscale mobility control or conformance. Compared to water injection, emulsion flooding can improve the macroscopic reservoir sweep as well as reduce the residual oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…However, this model can only simulate the retention of emulsion droplets under a small pressure gradient and low capillary number, and it cannot simulate the reflow of emulsion droplets under high pressure. Most of the mathematical models of emulsion seepage are modifications and improvements of the above mathematical models, such as the mathematical models established by Mandal and Bera 113 and Engelke et al 114 Lei et al 115,116 established an equation between the capture number and the residual oil saturation. A mathematical model of alkali/ surfactant/polymer (ASP) flooding is established, which includes the emulsification of crude oil.…”
Section: Numerical Simulation Of Macroscopic Seepagementioning
confidence: 99%
“…However, this model can only simulate the retention of emulsion droplets under a small pressure gradient and low capillary number, and it cannot simulate the reflow of emulsion droplets under high pressure. Most of the mathematical models of emulsion seepage are modifications and improvements of the above mathematical models, such as the mathematical models established by Mandal and Bera 113 and Engelke et al 114 Lei et al 115,116 established an equation between the capture number and the residual oil saturation. A mathematical model of alkali/ surfactant/polymer (ASP) flooding is established, which includes the emulsification of crude oil.…”
Section: Numerical Simulation Of Macroscopic Seepagementioning
confidence: 99%
“…Various core flooding experiments confirmed that injection of emulsions between two water floodings can improve the oil recovery by 20% or more (Demikhova et al, 2016;Kumar et al, 2012;Mandal et al, 2010b) .The mechanism responsible for the improved oil displacement involves the blocking by the emulsion's dispersed oil droplets of larger pore throats already swept by the water phase, which leads to diversion of subsequent water flow to smaller pores that are still fully saturated by oil (Mandal et al, 2010a;Soo et al, 1986;Soot and Radke, 1986), thus improving the homogeneity of the sweep (Chen et al, 2021;Pei et al, 2017) This diversion mechanism is only efficient if the size of emulsion droplets is matched to the pore throat width (Liu et al, 2019) In oil-wet rock formations, dewetting of oil adsorbed to rock surfaces by emulsification is another observed mechanism of oil mobilization (Ning et al, 2018) Guillen et al (Guillen et al, 2012) showed that emulsion flooding affects oil displacement by the water phase in a J o u r n a l P r e -p r o o f multi-scale fashion, by (i) lowering the mobility of the injected fluid, which leads to a more uniform macroscopic sweep, and (ii) better mobilization of trapped ganglia, which leads to a lower residual oil saturation. The multi-scale effect is clearly reflected in the relative permeability curves of oil and oil-in-water emulsion (a water phase containing dispersed oil droplets) flow presented by Engelke et al (Engelke, Bernardo and Carvalho, Marcio S and Alvarado, 2013) and in the saturation maps presented by de Farias et al (de Farias et al, 2016), which were obtained by X-ray tomography after water flooding and emulsion. The relative permeability curves of oil and an oil-in-water emulsion have been used in reservoirscale models to study oil displacement by emulsion injected or formed in situ (Arhuoma, Mohamed and Dong, Mingzhe and Yang, Daoyong and Idem, 2009;Ponce F. et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A água produzida com baixo teor de sólidos pode ser considerada uma emulsão de óleo em água salina. (Farias, 2013) McAuliffe (1973) Figura 2-6 -Imagens mostrando a mudança nos padrões de escoamento em um meio poroso após a injeção de emulsão (Guillen et al, 2012a) Outros experimentos apresentados por Guillen et al (2012a) Figura 2-9 -Gráficos com as permeabilidades relativas água-óleo e emulsão-óleo (Engelke et al 2013) Os mecanismos de mobilização de óleo com redução de óleo residual e melhora do varrido macroscópico promovidos pela injeção de emulsões precisam ser compreendidos e modelados para permitir a previsão de escoamento de reservatórios em cenários de injeção de emulsão. Ponce et al(2014) propuseram um modelo simplificado para representar os efeitos observados experimentalmente por Guillen et al (2012a,b) A descrição das equações que descrevem o escoamento em meios porosos será iniciada pelo modelo de fluxo em meios porosos mais simples onde existe apenas uma fase.…”
Section: Injeção De Emulsões Em Meios Porososunclassified
“…Figura 2-9 -Gráficos com as permeabilidades relativas água-óleo e emulsão-óleo (Engelke et al 2013) 35…”
unclassified